Resistance quaternary strata soil to static in the malecón Grau, district of Chorrillos - Lima - Gallarday, Tomás (2016)
This research is supported by technical reports located in the library of the Municipality of Chorrillos, as well as in public and private institutions such as the IGN, Ingemmet, Imarpe, Geophysical Institute of Peru, among others. We reviewed reports prepared by CIP experts, in addition to work carried out in the field, such as geological mapping of the Grau jetty scarp, systematic and detailed sampling in the visible soil strata. Two samples were taken to carry out mechanical studies and geochemical analyzes were made. The results allowed determining its granulometry, percentages of salts, sulfates and chlorides. Then, in the cabinet, the drawings were made, the ordering of the information brought from the field, such as the writing of this report, which suggests recommending to the local authority to give a longer useful life to the civil works that it plans to carry out on the Grau pier.